2015
DOI: 10.1002/eco.1686
|View full text |Cite
|
Sign up to set email alerts
|

Soil permeability, aggregate stability and root growth: a pot experiment from a soil bioengineering perspective

Abstract: Assessing the joint development of vegetation cover and soil properties is crucial to evaluate the efficiency of soil bioengineering techniques, especially during the most critical initial phase of vegetation colonization. We set up a laboratory experiment to quantify and disentangle the effect of Alnus incana roots on soil permeability and aggregate stability. Plants were grown in pots in a climate chamber for four different growing periods (1, 2, 4 and 8 months). Pots were filled with a soil coming from a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(56 citation statements)
references
References 47 publications
2
51
0
3
Order By: Relevance
“…Some previous field studies (van Noordwijk et al 1991;Mitchell et al 1995;Vergani and Graf 2015) also showed higher infiltration rate in vegetated soils than in the bare soil. However, it must be emphasised that these previous studies focused on one single mature plant (i.e., not multiple plants like the present study).…”
Section: Measured Saturated Hydraulic Conductivitymentioning
confidence: 61%
“…Some previous field studies (van Noordwijk et al 1991;Mitchell et al 1995;Vergani and Graf 2015) also showed higher infiltration rate in vegetated soils than in the bare soil. However, it must be emphasised that these previous studies focused on one single mature plant (i.e., not multiple plants like the present study).…”
Section: Measured Saturated Hydraulic Conductivitymentioning
confidence: 61%
“…Soil saturated hydraulic conductivity (SHC) is a key hydraulic property affecting different areas of interest from agriculture to forestry to slope stability and flood protection (Bens, Wahl, Fischer, & Hüttl, ; Rienzner & Gandolfi, ; Vergani & Graf, ). Saturated hydraulic conductivity is a critical parameter that controls how fast water can transmit while a soil is saturated, and it reflects soil conditions such as total porosity, pore size and tortuosity of pores, as well as characteristics of the soil water, including viscosity and density (Buelow, Steenwerth, & Parikh, ; Quirk & Schofield, ).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that planted treatments had more organo-mineral aggregates than the bare soil (without plants) that had the highest percentage of nonaggregated organic particles. This observation is related to the absence of the root system that is a key factor in promoting soil aggregation and stability of aggregates (Vergani and Graf 2016). Indeed, roots are known to stabilize surrounding aggregates through soil drying and root exudation with its associated microbial activity (Six et al 2004).…”
Section: Discussionmentioning
confidence: 99%